THE EFFECT OF COMPANY SIZE, ROA, ROE, AND DER ON F&B COMPANY CSR ON IDX 2017-2022 - Junita Monika Dachi; Ayang Pratama; Yeti Meliany Lubis (International Journal Labs, 2024)
Finding out what influences corporate social responsibility is the driving force behind this study, which aims to examine food and beverage companies listed on the Indonesian stock exchange. Organizational size, ROA, ROE, and debt-to-equity ratio are some of these considerations. This study's population consists of publicly traded food and beverage companies in Indonesia. Researchers in this study used a purposive sampling technique that included a random selection of 30 companies. The procedures used in this investigation to test different hypotheses include a coefficient of determination, a t-test, an f-test, and multiple linear regression analysis. A negative and statistically significant effect of the debt-to-equity ratio on CSR exists, even though the study found that ROA and ROE had no effect on CSR. Companies in Indonesia's food and beverage industry that are public face different levels of CSR scrutiny based on metrics like company size, ROA, ROE, and debt-to-equity ratio, among others